Dispersal patterns in black howler monkeys (Alouatta pigra): Integrating multiyear demographic and molecular data. Issue 1 (1st November 2021) - Van Belle, Sarie; Di Fiore, Anthony
Abstract: Dispersal is a fundamental process in the functioning of animal societies as it regulates the degree to which closely related individuals are spatially concentrated. A species' dispersal pattern can be complex as it emerges from individuals' decisions shaped by the cost–benefit tradeoffs associated with either remaining in the natal group or dispersing. Given the potential complexity, combining long‐term demographic information with molecular data can provide important insights into dispersal patterns of a species. Based on a 15‐year study that integrates multiyear demographic data on six groups with longitudinal and cross‐sectional genetic sampling of 20 groups ( N  = 169 individuals, N  = 21 polymorphic microsatellite loci), we describe the various dispersal strategies of male and female black howler monkeys ( Alouatta pigra ) inhabiting Palenque National Park, Mexico. Genetically confirmed dispersal events ( N  = 21 of 59 males; N  = 6 of 65 females) together with spatial autocorrelation analyses revealed that the dispersal pattern of black howlers is bisexual with strong sex‐biases in both dispersal rate (males disperse more often than females) and dispersal distance (females disperse farther than males). Observational and genetic data confirm that both males and females can successfully immigrate into established groups, as well as form new groups with other dispersing individuals. Additionally, both males and females may disperse singly, as well as in pairs, and both may also disperse secondarily. Overall, our findings suggest multiple dispersal trajectories for black howler males and females, and longer multiyear studies are needed to unravel which demographic, ecological and social factors underlie individuals' decisions about whether to disperse and which dispersal options to take. Resumen: La dispersión es un proceso fundamental en el funcionamiento de las sociedades animales, ya que regula el grado en que los individuos parentados se concentran espacialmente. El patrón de dispersión de una especie puede ser complejo ya que surge de las decisiones de los individuos conformadas por las compensaciones de costo‐beneficio asociadas con permanecer en el grupo natal o dispersarse. Dada esta posible complejidad, la combinación de información demográfica a largo plazo con datos moleculares puede proporcionar información importante sobre los patrones de dispersión de una especie en particular. Basado en un estudio de 15 años que integra datos demográficos de seis grupos sociales con muestreo genético longitudinal y transversal de 20 grupos ( N  = 169 individuos, N  = 21 loci de microsatélites polimórficos), describimos las diversas estrategias de dispersión de machos y hembras del mono aullador negro ( Alouatta pigra ) que habitan el Parque Nacional Palenque, México. Los eventos de dispersión confirmados genéticamente ( N  = 21 de 59 machos; N  = 6 de 65 hembras), junto con los análisis de autocorrelación espacial revelaron que el patrón de dispersión de los monos aulladores negros es bisexual con fuertes sesgos sexuales en ambas tasas de dispersión (los machos se dispersan más a menudo que las hembras) y distancia de dispersión (las hembras se dispersan más lejos que los machos). Los datos de observación y genéticos confirman que tanto machos como hembras pueden inmigrar con éxito a grupos ya establecidos, así como formar nuevos grupos con otros individuos que se están dispersando. Además, tanto los machos como las hembras pueden dispersarse individualmente, así como en parejas, y ambos también pueden dispersarse secundariamente. En general, nuestros hallazgos sugieren múltiples trayectorias de dispersión para aulladores negros de los dos sexos, y se necesitan más estudios para desentrañar qué factores demográficos, ecológicos y sociales subyacen en las decisiones de los individuos sobre si dispersarse y qué opciones de dispersión tomar.